Kerr and Faraday rotations in topological flat and dispersive band structures - Alireza Habibi; Ahmad Z Musthofa; Elaheh Adibi; Johan Ekström; Thomas L Schmidt; Eddwi H Hasdeo (New Journal of Physics, 2022)
Integer quantum Hall (IQH) states and quantum anomalous Hall (QAH) states show the same static dc response but distinct dynamical ac response. In particular, the ac anomalous Hall conductivity profile σ _yx ( ω ) is sensitive to the band shape of QAH states. For example, dispersive QAH bands shows resonance profile without a sign change at the band gap while the IQH states shows the sign change resonance at the cyclotron energy. We argue by flattening the dispersive QAH bands, σ _yx ( ω ) should recover to that of flat Landau bands in IQH, thus it is necessary to know the origin of the sign change. Taking a topological lattice model with tunable bandwidth, we found that the origin of the sign change is not the band gap but the van Hove singularity energy of the QAH bands. In the limit of small bandwidth, the flat QAH bands recovers σ _yx ( ω ) of the IQH Landau bands. Because of the Hall response, these topological bands exhibit giant polarization rotation and ellipticity in the reflected waves (Kerr effect) and rotation in the order of fine structure constant in the transmitted waves (Faraday effect) with profile resembles σ _yx ( ω ). Our results serve as a simple guide to optical characterization for topological flat bands.